Precursor-directed Biosynthesis in Tabernaemontana catharinensis as a New Avenue for Alzheimerʼs Disease-modifying Agents - Musquiari, Bruno; Crevelin, Eduardo J.; Bertoni, Bianca W.; França, Suzelei de C.; Pereira, Ana Maria S.; Castello, Ana Carolina Devides; Castillo-Ordoñez, Willian O.; Giuliatti, Silvana; Lopes, Adriana A. (Planta Medica, 2020)
Plants produce a high diversity of metabolites that can act as regulators of cholinergic dysfunction. Among plants, the potential of species of the genus Tabernaemontana to treat neurological disorders has been linked to iboga-type alkaloids that are biosynthesized by those species. In this context, precursor-directed biosynthesis approaches were carried out using T. catharinensis plantlets to achieve new-to-nature molecules as promising agents against Alzheimerʼs disease. Aerial parts of T. catharinensis, cultured in vitro, produced 7 unnatural alkaloids (5-fluoro-ibogamine, 5-fluoro-voachalotine, 5-fluoro-12-methoxy-Nb-methyl-voachalotine, 5-fluoro-isovoacangine, 5-fluoro-catharanthine, 5-fluoro-19-(S)-hydroxy-ibogamine, and 5-fluoro-coronaridine), while root extracts showed the presence of the same unnatural iboga-type alkaloids and 2 additional ones: 5-fluoro-voafinine and 5-fluoro-affinisine. Moreover, molecular docking approaches were carried out to evaluate the potential inhibition activity of T. catharinensis’ natural and unnatural alkaloids against AChE and BChE enzymes. Fluorinated iboga alkaloids (5-fluoro-catharanthine, 5-fluoro-voachalotine, 5-fluoro-affinisine, 5-fluoro-isovoacangine, 5-fluoro-corinaridine) were more active than natural ones and controls against AchE, while 5-fluoro-19-(S)-hydroxy-ibogamine, 5-fluoro-catharanthine, 5-fluoro-isovoacangine, and 5-fluoro-corinaridine showed better activity than natural ones and controls against BChE. Our findings showed that precursor-directed biosynthesis strategies generated “new-to-nature” alkaloids that are promising Alzheimerʼs disease drug candidates. Furthermore, the isotopic experiments also allowed us to elucidate the initial steps of the biosynthetic pathway for iboga-type alkaloids, which are derived from the MEP and shikimate pathways.
Keywords: Tabernaemontana catharinensis; Apocynaceae; iboga-alkaloids; Alzheimerʼs; fluorinated analogues; molecular docking; cholinergic dysfunction; cholinesterase inhibitors